Pengaruh Palm Oil Fuel Ash terhadap Kuat Tekan dan Daya Serap Air pada Bata Ringan Tipe CLC - Amry Dasar; Dahlia Patah; Nur Okviyani; Michail Amin (Jurnal Konstruksi, 2026)
Cellular lightweight concrete (CLC) blocks are a type of non-structural wall material that has the potential to reduce a building’s dead load; however, their use still faces technical challenges due to low compressive strength and high water absorption. Palm oil fuel ash (POFA) derived from oil palm biomass waste has the potential to be used as a partial cement substitute. This study aims to evaluate the effect of POFA as a partial cement substitute at levels of 0–30% on the compressive strength and water absorption of CLC lightweight bricks. POFA was ground twice using a disc mill with a No. 200 sieve. Cube specimens measuring 50×50×50 mm were tested at 7 and 28 days of age under normal curing and steam curing conditions. The results showed that a 10% POFA substitution yielded the best performance, with a compressive strength of 3.53 MPa under normal curing at 28 days and 3.57 MPa under steam curing at 28 days. This mixture also produced the lowest water absorption, namely 21.58% and 1.66% under the same conditions. The highest strength activity index was also achieved with a 10% POFA substitution. These findings indicate that the use of 10% POFA is suitable for producing low-cement CLC lightweight bricks with better mechanical and absorption performance for sustainable non-structural wall applications.